Management of a large retroperitoneal primitive neuroectodermal tumour: 'a multimodal approach'. (28th February 2012) - Sable, Shailesh; Gandhi, Vidhyachandra; Nagral, Aabha; Nagral, Sanjay
Abstract : Retroperitoneal primitive neuroectodermal tumour (PNET) is a rare disease having poor prognosis. Treatment mainly consists of en block resection of the tumour to achieve RO resection, however multimodal approach has also been used with improved survival. The authors report a 40-year-old male with large retroperitoneal PNET adherent to aorta and compressing the inferior vena cava. He was subjected to P6 protocol chemotherapy (cyclophosphamide, adriamycin, vincristine, ifosfamide and etoposide) in view of borderline operability. Postchemotherapy contrast enhanced CT revealed significant reduction in size of the lesion. He underwent complete resection of the tumour followed by concurrent chemoradiation. He remains asymptomatic on follow-up over a period of 2 years.